Once Upon an Eskimo Time - Wilder, Edna, 1916-2011 (Book collections on Project MUSE., 2009)
Continuing the sacred tradition of her ancestors, in Once Upon an Eskimo Time Edna Wilder retells a year in her Eskimo mother's life. Wilder eloquently captures the oral storytelling traditions of her people, and she employs descriptions of the weather and harsh climates of Alaska's Norton Sound to illustrate the hardiness of her mother's spirit. Family values, subsistence living, and the cycle's of life form a narrative that captures the now-vanished lifestyle along the Bering Sea. "Readers of whatever age will enjoy Nedercook's delightful account of the day-to-day, legends, and be.